Qualitative Study on Leadership, Teacher Performance, and School Environment in Academic Improvement - Fitanto, Idhi; Widiyanto (Universitas Negeri Semarang, 2025)
This research explores the collective influence of school leadership, teacher performance, and a child-centered educational environment on students’ academic success at SD Negeri Dawuhan 03, Sirampog, Brebes. Adopting a qualitative case study approach, data were gathered through semi-structured interviews, immersive observations, and document reviews. Participants included school leaders, instructional staff, and learners. The findings suggest that collaborative and reflective leadership practices substantially enhance the educational experience. The principal's role extended beyond administration, acting as a guide and motivator for teacher innovation. Teachers with strong pedagogical skills, continuous engagement in professional learning, and inclusive classroom strategies had a significant positive impact on student learning. Furthermore, the implementation of child-friendly principles such as inclusive spaces, mental health support, and a zero-tolerance policy on bullying was instrumental in maintaining learner engagement and attendance. Despite these efforts, challenges such as limited resources, inadequate supervision during recess, and uneven parental involvement persisted. Ultimately, academic improvement was found to be most successful when leadership, teaching quality, and school climate worked cohesively. The study offers practical implications for policy initiatives aimed at strengthening primary education outcomes.